2016
DOI: 10.1016/j.mambio.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anthropogenic disturbance on the density and activity pattern of deer evaluated with respect to spatial scale-dependency

Abstract: This study examined the influence of anthropogenic disturbance (agriculture, forestry, hunting and feral domestic dogs) on the population density and daily activity pattern of deer.We quantified the effects of land use (broad-leaved forest, mixed coniferous/broad-leaved forest, natural grassland, subalpine vegetation, forestry area, and agricultural land), along with hunting pressure, and densities of feral domestic dogs and wild macaques on deer. The effects of land use were analyzed at various spatial scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Another study in Japan reported that the nocturnal activity of sika deer was increased by the presence of agricultural land and forestry area but not by hunting activity 22 . In contrast, a study revealed that sika deer showed nocturnal activity during the non-hunting and hunting seasons, their activity was reduced by hunting activity, and their nocturnal activity increased close to human settlements 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Japan reported that the nocturnal activity of sika deer was increased by the presence of agricultural land and forestry area but not by hunting activity 22 . In contrast, a study revealed that sika deer showed nocturnal activity during the non-hunting and hunting seasons, their activity was reduced by hunting activity, and their nocturnal activity increased close to human settlements 21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have compared the impact of different levels of hunting intensities on the activity patterns of ungulates, because it is difficult to control hunting activity and alter hunting programs easily. Although a previous study in Japan reported that crepuscular activity increased with hunting pressure 22 , it is difficult to obtain detailed information on the number of hunted deer, hunting times, hunting sites, and hunting methods. Thus, we conducted a culling program with several levels of culling intensity.…”
Section: Introductionmentioning
confidence: 99%